Implementing the “Show-and-Tell” Method to Improve Students’ Speaking Skills - Hasna Salsabila; Muhamad Ahsanu; Mustasyfa Thabib Kariadi; Slamet Riyadi (LPPM Universitas Pekalongan, 2023)
This study aimed to find out the implementation of the